2018
DOI: 10.1093/nar/gky1044
|View full text |Cite
|
Sign up to set email alerts
|

Translocatome: a novel resource for the analysis of protein translocation between cellular organelles

Abstract: Here we present Translocatome, the first dedicated database of human translocating proteins (URL: http://translocatome.linkgroup.hu). The core of the Translocatome database is the manually curated data set of 213 human translocating proteins listing the source of their experimental validation, several details of their translocation mechanism, their local compartmentalized interactome, as well as their involvement in signalling pathways and disease development. In addition, using the well-established and widely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…1b). Moreover, using a dataset of 1233 known and machine learning-predicted translocating proteins from the Translocatome database 24 , we found that 41.2% EMF proteins (98 out of 238) could change their subcellular localization upon a regulatory event, representing, again, a higher fraction than in the PPI network (9%, two-sided Fisher's Exact Test, OR = 7.8, P-value < 2.2 x 10 -16 ) (Fig. 1b).…”
Section: Emf Proteins As a Model To Study The Regulation Of Protein Lmentioning
confidence: 99%
“…1b). Moreover, using a dataset of 1233 known and machine learning-predicted translocating proteins from the Translocatome database 24 , we found that 41.2% EMF proteins (98 out of 238) could change their subcellular localization upon a regulatory event, representing, again, a higher fraction than in the PPI network (9%, two-sided Fisher's Exact Test, OR = 7.8, P-value < 2.2 x 10 -16 ) (Fig. 1b).…”
Section: Emf Proteins As a Model To Study The Regulation Of Protein Lmentioning
confidence: 99%
“…We also observed that 111 EMF proteins (46.6% of the total) belong to the multilocalizing proteome, defined by immunofluorescence-based approaches in the Human Protein Atlas (HPA) ( 31 ), a significantly higher fraction than in the PPI network (36.7%, two-sided Fisher's Exact Test, odds ratio (OR) = 1.52, P -value = 1.7 × 10 −3 ) (Figure 1B ). Moreover, using a dataset of 1233 known and machine learning-predicted translocating proteins from the Translocatome database ( 34 ), we found that 41.2% EMF proteins (98 out of 238) could change their subcellular localization upon a regulatory event, representing, again, a higher fraction than in the PPI network (9%, two-sided Fisher's Exact Test, OR = 7.8, P -value<2.2 × 10 −16 ) (Figure 1B ). Overall, this indicates that EMF proteins are more often localized in different cellular districts than expected, a feature that may be regulated by alternative 3′UTRs.…”
Section: Resultsmentioning
confidence: 99%
“…By integrating our knowledge of protein localization during HCMV infection 12 and the translocatome dataset 55 , we observed that many proteins predicted to translocate do not display altered aggregation profiles. It is possible that some translocation events occur via endosomal trafficking of complexes, rather than individual protein movements.…”
Section: Prm Validation Igf2rmentioning
confidence: 99%
“…Therefore, we interrogated our data to determine if proteins known or predicted to translocate display changes in aggregation properties. We assessed two resources of translocating proteins-the translocatome database 55 (translocations outside the context of infection) and our report of potentially translocating proteins during HCMV infection 12 (Supplementary Data 5). Surprisingly, for both datasets, most Tm values were not changed at any infection time point compared to mock ( Fig.…”
Section: Articlementioning
confidence: 99%